2016
DOI: 10.1128/aac.01595-15
|View full text |Cite
|
Sign up to set email alerts
|

An Aromatic Diamidine That Targets Kinetoplast DNA, Impairs the Cell Cycle in Trypanosoma cruzi, and Diminishes Trypomastigote Release from Infected Mammalian Host Cells

Abstract: dTrypanosoma cruzi is the etiological agent of Chagas disease, affecting approximately 10 million people in the Americas and with some 40 million people at risk. The objective of this study was to evaluate the anti-T. cruzi activity of three new diamidines that have a 3,4-ethylenedioxy extension of the thiophene core, designated MB17, MB19, and MB38. All three diamidines exhibited dose-dependent inhibition of epimastigote replication. The mechanisms of action of these diamidines were investigated. Unlike MB17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…To determine whether IR treatment led to DNA strand breaks, a terminal deoxynucleotidyl transferase dUTP nick end-labeling (TUNEL) assay was performed according to protocols that were already standardized in trypanosomatids 16 , 32 , 33 (see the material and methods section). After IR treatment, the parasites were TUNEL labeled, and their fluorescence intensity was quantified by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether IR treatment led to DNA strand breaks, a terminal deoxynucleotidyl transferase dUTP nick end-labeling (TUNEL) assay was performed according to protocols that were already standardized in trypanosomatids 16 , 32 , 33 (see the material and methods section). After IR treatment, the parasites were TUNEL labeled, and their fluorescence intensity was quantified by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…An alteration of the cell cycle consisting of the accumulation of parasites in the G/M phase could be a hallmark for DNA damage (31,38). Our results revealed that BT10-and BT3-treated cells (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…The infection index was calculated as the arithmetical product of the percentage of infected cells and the number of parasites per cell. The effect of BT10 on trypomastigote production was determined by collecting samples of the extracellular medium on the fifth day postinfection and counting the number of trypomastigotes in a Neubauer chamber (38). The results correspond to the means from three independent experiments, each performed in triplicate.…”
Section: Synthesis Of Drugs and Chemical Characterizationmentioning
confidence: 99%
“…Pentamidine has been shown to interact with RNA to disrupt group I intron splicing and translation, leading to reduced cell growth in fungi [37,38,39]. Furthermore, based on interactions with DNA, pentamidine is also thought to inhibit kinetoplast DNA replication, as has been observed of related aromatic diamidine compounds in trypanosomes [36,40,41]. In relation to DM1, pentamidine treatment of a HeLa DM1 cell model transiently expressing r(CUG) 960 revealed a reduction in MBNL:r(CUG) EXP foci and the rescue of INSR exon 11 and cardiac troponin T ( cTNT ) exon 5 MBNL-dependent minigene mis-splicing events [35].…”
Section: Screening Small Molecule Libraries To Target Toxic Cug Rnamentioning
confidence: 99%